HOW DO INTELLECTUAL CAPITAL DISCLOSURES MEDIATE FINANCIAL STRUCTURE AND COMPANY PERFORMANCE? EVIDENCE FROM INDONESIA AND SINGAPORE - Yusphita, Dea Mitzi; Ekawati, Erni (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
This study examines the effect of disclosure of intellectual capital in mediating the financial structure and performance of companies using path analysis method. This study also compares the effect of disclosing intellectual capital on companies listed on the Indonesian and Singapore stock exchanges from 2018 to 2020. A two-stage least squares statistical model is used to test the research hypothesis. The findings show that the financial structure in Indonesia and Singapore has a significant negative effect on financial performance. Meanwhile, financial structure has a significant negative effect on market performance only in Singapore, while Indonesia has no effect. Disclosure of intellectual capital which is used as a mediating variable on financial structure and performance has a significant positive effect in Singapore. Meanwhile, there is no significant effect on the relationship between financial structure and market performance after being mediated by disclosure of intellectual capital. This study can be used by managers as a starting point for designing more effective methods of using intellectual capital to gain competitive advantage through leverage.JEL: M41, O34.